2014
DOI: 10.1016/j.gheart.2014.04.002
|View full text |Cite
|
Sign up to set email alerts
|

Why Did Ancient People Have Atherosclerosis? From Autopsies to Computed Tomography to Potential Causes

Abstract: Computed tomographic findings of atherosclerosis in the ancient cultures of Egypt, Peru, the American Southwest and the Aleutian Islands challenge our understanding of the fundamental causes of atherosclerosis. Could these findings be true? Is so, what traditional risk factors might be present in these cultures that could explain this apparent paradox? The recent computed tomographic findings are consistent with multiple autopsy studies dating as far back as 1852 that demonstrate calcific atherosclerosis in an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 52 publications
2
19
0
2
Order By: Relevance
“…The first point to emphasize is that cardiovascular diseases, predominately ischemic heart disease and strokes caused by atherosclerosis, remain the major causes of death in our society (www.cdc.gov/nchs/fastats/leading-causes-of-death.htm). Second, the detection of high frequencies of calcified arterial lesions among the remains of humans who populated ancient civilizations is consistent with the hypothesis that it has always been an important disease of our species (Thomas et al 2014). Third, aging is quite clearly a major risk factor in the emergence of the disease (Wang and Bennett 2012).…”
Section: Age-related Macular Degenerationsupporting
confidence: 78%
“…The first point to emphasize is that cardiovascular diseases, predominately ischemic heart disease and strokes caused by atherosclerosis, remain the major causes of death in our society (www.cdc.gov/nchs/fastats/leading-causes-of-death.htm). Second, the detection of high frequencies of calcified arterial lesions among the remains of humans who populated ancient civilizations is consistent with the hypothesis that it has always been an important disease of our species (Thomas et al 2014). Third, aging is quite clearly a major risk factor in the emergence of the disease (Wang and Bennett 2012).…”
Section: Age-related Macular Degenerationsupporting
confidence: 78%
“…The journal Global Heart devoted a large portion of the June 2014 issue to atherosclerosis in ancient humans. Computed tomography studies found that ancient humans had extensive atherosclerosis, even though the people analyzed were from different locations, had a wide range of diets and lifestyles, and died at relatively young ages 61, 62 . The researchers proposed that chronic inflammation induced by microbial and parasitic diseases might have been responsible 61, 62 .…”
Section: Is the Only Good H Pylori A Dead H Pylori?mentioning
confidence: 99%
“…Computed tomography studies found that ancient humans had extensive atherosclerosis, even though the people analyzed were from different locations, had a wide range of diets and lifestyles, and died at relatively young ages 61, 62 . The researchers proposed that chronic inflammation induced by microbial and parasitic diseases might have been responsible 61, 62 . The incidence of myocardial infarctions decreased significantly in the second half of the 20th century in the US, indicating a concomitant change in an important environmental factor(s) involved in arthrosclerosis 63 .…”
Section: Is the Only Good H Pylori A Dead H Pylori?mentioning
confidence: 99%
“…Since lifestyle or clinical factors could not explain these effects, the authors propose that differences in genetic background or environmental aspects could influence the susceptibility to increased arterial stiffness in certain populations. In support of this hypothesis, a recent review described autopsy and computed tomography studies showing the presence of peripheral arterial calcifications and atherosclerosis in four different ancient cultures; a finding that challenges the concept that atherosclerosis is a modern disease associated with current risk factors, and that supports that humans may have an inherent genetic susceptibility to arterial degeneration which may be accelerated or precipitated by environmental factors (Thomas et al 2014). For a more comprehensive review on genetic variants predisposing to arterial stiffness, see Logan et al (2015).…”
Section: Factors Associated With Increased Arterial Stiffnessmentioning
confidence: 99%